2015
DOI: 10.1080/14735903.2015.1026047
|View full text |Cite
|
Sign up to set email alerts
|

Integrated soil fertility management: from concept to practice in Eastern DR Congo

Abstract: Journal articleIFPRI3; ISI; A Ensuring Sustainable food production; CRP2DSGD; PIMPRCGIAR Research Program on Policies, Institutions, and Markets (PIM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…The progress from this initiative shows that using diverse soil fertility practices which are based on local conditions, do not only improve the productivity of crops but also enhance the livelihood of small-scale farmers. According to the recent adoption study on 420 farms in the Democratic Republic of Congo, only few farmers reached full ISFM indicating sequential technology adoption rather than simultaneous [148].…”
Section: Soil Managementmentioning
confidence: 99%
“…The progress from this initiative shows that using diverse soil fertility practices which are based on local conditions, do not only improve the productivity of crops but also enhance the livelihood of small-scale farmers. According to the recent adoption study on 420 farms in the Democratic Republic of Congo, only few farmers reached full ISFM indicating sequential technology adoption rather than simultaneous [148].…”
Section: Soil Managementmentioning
confidence: 99%
“…Through a review of available literature on agricultural technology adoption, Lambrecht et al . () discuss the practical patterns of interrelated technology adoption, which can be differentiated into: independent, sequential, or simultaneous. For the independent decisions, the probability of applying one technology is not affected by adoption of another technology.…”
Section: Methodsmentioning
confidence: 99%
“…Lambrecht et al . () further notes that besides the technical aspects, socioeconomic factors such as awareness, availability, input requirements, risk, and local practices could affect the adoption patterns. Accounting for these unobserved factors and inter‐relationships among adoption decisions regarding different components reduces bias and improves the estimate (Belderbos et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The increase in population density and the overexploitation of land without proper nutrient management are increasingly leading to severe impoverishment of soil fertility and erosion (Pypers, Sanginga et al, 2011), which has a direct impact on land productivity and ultimately on poverty and food insecurity (Lambrecht, Vanlauwe et al, 2016b).…”
Section: Jenga II Technologies Promotedmentioning
confidence: 99%
“…Given the pressing need for agricultural intensification and productivity growth in Eastern DRC (Lambrecht, Vanlauwe et al, 2016b), as the conflict has eased in the last 10 years several organizations have strived to expose farmers to new agricultural technologies (Rossi, Hoerz et al, 2006), and a number of authors have studied their impact in the context of integrated soil fertility management (ISFM) (Lambrecht, Vanlauwe et al, 2016a, 2016bSchut, van Asten et al, 2016;Vanlauwe & Zingore, 2011). Pypers, Sanginga et al (2011) found that in central Africa, the productivity and net economic returns of cassava-legume intercropping could be increased with the joint introduction of different components of ISFM, including proper agronomic practices such as row planting, the use of disease-free improved germplasm, adequate crop arrangement, and fertilizer application.…”
Section: Jenga II Technologies Promotedmentioning
confidence: 99%